Neuroimaging in the Evaluation of Epilepsy - Velez-Ruiz, Naymee J.; Klein, Joshua P. (Seminars in Neurology, 2012)
Neuroimaging has provided extraordinary insight into the pathologic substrate of epilepsy. The excellent spatial resolution and soft tissue contrast of magnetic resonance imaging (MRI) allows identification of a substantial number of pathologies including hippocampal sclerosis, malformations of cortical development, low grade tumors, and vascular abnormalities, among others. Complementary imaging modalities such as positron emission tomography, single photon emission computed tomography, and magnetoencephalography can be diagnostically helpful as well. Identification of a pathologic substrate is particularly important in patients with medically refractory epilepsy who are undergoing evaluation for surgery, and essential in determining the likelihood of seizure freedom after surgical intervention. This article reviews current and emerging neuroimaging techniques in the field of epilepsy.
Keywords: epilepsy; hippocampal sclerosis; cortical malformation; brain tumor; cavernous angioma; neurocutaneous disorder; traumatic brain injury